Dabartinės lietuvių kalbos daiktavardinių veiksmažodžių priesagų ir jų pamatinių daiktavardžių kaitybos klasių santykis - Pakerys, Jurgis (Baltistica, 2011)
The relation between the suffixes of denominal verbs and the inflection classes of their base nouns in modern LithuanianIt is well known that Lithuanian verbal suffixes -ėti, -y-ti, -o-ti, and -uo-ti are historically related to nominal stems ē, ī, ā, and o respectively. At an earlier stage, the suffix *-éó was added to nominal stems and this addition simply transferred them to the class of verbs without any predictable derivational meaning (cf. Meillet 1937, 219). Later on, the former theme vowels were reanalyzed as verbal (neo-)suffixes, but the relation to certain nominal stems (= inflection classes) still remained to some extent (Skardžius 1943, 488, 493, 504, 509, 521, 534f.; Stang 1966, 360, 364, 366), cf. historically regular seil--ti ‘slobber, slaver’ (← séilės ‘saliva’), vag-óti ‘furrow’ (← vagà ‘furrow’), ak-ýti ‘get holes, become porous’ (← aks ‘eye’), žaibúoti ‘flash (of lightning)’ (← žabas ‘lightning’) alongside (historically) nonregular kand--ti ‘be destroyed by moths’ (← kánds ‘moth’), seili-óti ‘slaver’ (← séilės ‘saliva’), dm-y-ti ‘emit smoke’ (← dmai ‘smoke’), etc.In this paper, all synchronically derivationally transparent denominal verbs with -ėti, -y-ti, -o-ti, and -uo-ti found in the dictionary of Modern Lithuanian (DŽ6e) were analyzed and qualified in respect of the relation between the suffix and its historically correlated nominal stem.It is clear that in Modern Lithuanian the distinction can be made between the suffixes with (а) weak (-ėti, -y-ti) and (b) strong (-(i)o-ti, -(i)uo-ti) relation to the corresponding noun inflection classes -ė, -i-, -(i)o-, and -(i)a-. In the case of group (a), the nouns of historically predictable inflection classes constitute ca. 20–30% of the bases, while in the case of group (b), these classes take up ca. 70% (cf. Tables 1–4).The denominal formations in -ėti (especially the ones which are not based on inflection class ė) have an easily predictable inchoative meaning, but this has to be an extension of use of inchoative deadjectival -ėti (< *-eh1-) rather than “semantization” of nominal thematic suffix -ė. In the case of other suffixes, some meanings such as factitive are quite frequent, but they cannot be qualified as specialized and predictable.
Keywords: –